The Effectiveness of Pregnant Exercise Against Anxiety Levels in Promigravida Pregnant Women at Pratama Deliana Clinic Pekanbaru - Rina Yulviana; Intan Widya Sari (Journal of Midwifery and Nursing, 2021)
Pregnancy exercise is one of the recommended sports for pregnant women to do because it aims to prepare a pregnant woman mentally and physically. Disorders during pregnancy that usually occur are poor sleep quality, high levels of maternal anxiety, low back pain, increased urinary frequency and leg cramps.Experienced anxiety pregnant women are about pregnancy, childbirth, and its role as a mother. Pregnant women will also transmit their emotional physical effects to the fetus. If the anxiety increases, it will affect the fetus. The purpose of this study was to determine the effectiveness of pregnancy exercise on the level of anxiety in pregnant women. This type of research is Quasi experimental. The population in this study were pregnant women at the Pratama Deliana Clinic Pekanbaru. The results showed that pregnancy exercise was effective in reducing anxiety levels in pregnant women with a p-value of 0.002 (<0.05). It can be concluded that there is a significant difference in the level of anxiety of pregnant women between before doing pregnancy exercise and after doing pregnancy exercise in pregnant women. It is recommended that the clinic be able to do promotions about pregnancy exercise through banners, leaflets,